Controllable Design of Structural and Mechanical Behaviors of Al–Si Foams by Powder Metallurgy Foaming. Issue 10 (22nd May 2022) - Yang, Xudong; Xie, Mingrui; Li, Weiting; Sha, Junwei; Zhao, Naiqin
Abstract : Silicon (Si) has a significant influence on the cellular structure and microstructure of the aluminum (Al) foams, which in turn will notably affect their mechanical responses. Herein, the Al–Si foams are fabricated via a novel powder metallurgy foaming approaches with multiple Si contents to investigate the role of Si concentrations on the structural and mechanical properties. The results show that the certain contents of Si can not only delay the expansion process, but also increase the maximum expansion rate to improve the cellular structure. Specifically, the AlSi7 foams process the optimal comprehensive compressive properties of yield stress (4.36 MPa), plateau stress (6.02 MPa), and energy absorption capacity (3.47 MJ m −3 ) with the relative density of 0.15. However, excessive Si can decrease the expansion rate and deteriorate the cellular structure. Moreover, the deformation mode of the Al foams during compressive process converts from plastic mode to brittle mode by the adding of Si. Generally, the AlSi7 foams possess an excellent trade‐off between toughness and brittleness and exhibit the optimal mechanical responses. Abstract : Silicon affects the cellular structure and microstructure of the aluminum foams. The Al–Si foams are fabricated via a novel powder metallurgy foaming approaches with multiple Si contents to investigate the role of Si concentrations on the structural and mechanical properties. AlSi7 foams possess an excellent trade‐off between toughness and brittleness and exhibit the optimal mechanical responses.